A high selectivity dual‐band bandpass filter using quadruple‐mode multi‐stub loaded ring resonator (SLRR). Issue 7 (29th March 2021) - Sun, Mingli; Chen, Zhijiao; Zuo, Tao; Zuo, Zhaoyu; Zhang, Anxue
Abstract: A high selectivity dual‐band filter is proposed based on the quadruple‐mode multi‐stub loaded ring resonator. The ring resonator can utmostly avoid bending the electromagnetic wave. Two external open stubs are employed to generate four transmission poles where the odd‐ and even‐mode is utilized to analyze the resonant frequencies of the BPF. The internal stub effectively reduces the insert loss (IL) by improving the external quality factor Q e of the second passband. In addition, five transmission zeros are generated due to the multipath and self‐resonance modes to improve the out‐of‐band selectivity of the proposed filter. The proposed filter centered at 2.65 and 4.84 GHz is designed, fabricated and measured. The simulated results agree well with the measured results.